On the Optimal Inventory Equation - Bellman, R.; Glicksberg, I.; Gross, O. (Management Science, 1955)
The purpose of this paper is to discuss a number of functional equations which arise in the “optimal inventory” problem. This is a particular case of the general problem of ordering in the face of an uncertain future demand. Actually, an important aspect of the problem is that of determining a suitable criterion of cost, one which is both realistic and analytically malleable.